2012
DOI: 10.1590/s1415-52732012000500008
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de professores e estudante em relação ao perfil de formação de nutricionista em saúde pública

Abstract: OBJETIVO: Analisar a percepção de professores e estudantes em relação ao perfil de formação do nutricionista em saúde pública. MÉTODOS: A pesquisa, de abordagem qualiquantitativa, foi realizada com participantes do 21° Congresso Brasileiro de Nutrição. Foi aplicado um questionário com estudantes e recémegressos, e feito um grupo focal com professores. Foi estabelecida a análise descritiva dos dados quantitativos, e a análise qualitativa foi desenvolvida por meio da análise do discurso do sujeito coletivo. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
25

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 9 publications
0
11
0
25
Order By: Relevance
“…However, complementary analyzes of the current study did not identify differences in the knowledge of technical materials nor in the performance of actions of the nutrition area among those with and without graduate courses (data not shown). The training of the nutritionist directed to PHC is essential to minimize the difficulties of articulation between teaching and health service of the undergraduate courses in Nutrition [21]. The lack of training may be related to the precarious and temporary contracting of nutritionists, which, in turn, may lead them to exercise the profession in other places or areas of activity, characteristics found both in this (nine had another employment relationship) and in other studies [18,20].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, complementary analyzes of the current study did not identify differences in the knowledge of technical materials nor in the performance of actions of the nutrition area among those with and without graduate courses (data not shown). The training of the nutritionist directed to PHC is essential to minimize the difficulties of articulation between teaching and health service of the undergraduate courses in Nutrition [21]. The lack of training may be related to the precarious and temporary contracting of nutritionists, which, in turn, may lead them to exercise the profession in other places or areas of activity, characteristics found both in this (nine had another employment relationship) and in other studies [18,20].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, a previous study found that most nutritionists are familiar with the Food Guide for the Brazilian Population, the Food and Nutrition Surveillance Protocol, and the National Food and Nutrition Policy, but there are few who know the Matrix of food and nutrition actions in Primary Care [21]. The proper use of these materials enables the correct diagnosis of the nutritional status and the identification of associated risks [25].…”
Section: Discussionmentioning
confidence: 99%
“…O nutricionista é um profissional generalista da área da saúde responsável pela promoção da segurança alimentar e atenção nutricional em todos os seus campos de atuação, contribuindo na manutenção e recuperação do estado nutricional de indivíduos e coletividades [1][2][3] .…”
Section: Introductionunclassified
“…Esse debate suscitou a publicação nos últi-mos cinco anos (2009 a abril de 2014) de considerável número de artigos (n=22) sobre o processo de formação e de atuação profissional do nutricionista no Brasil [2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Em relação ao processo específico de formação do nutricionista na área de Saúde Coletiva, foram identificados sete artigos publicados nos últimos cinco anos 2,3,6,7,9,10,18 , observando-se distintos desenhos e enfoques analíticos entre estes sete artigos, desde aqueles com abordagens teórico-conceituais 2,3,7 , àqueles centrados em abordagens empíricas 6,9,10,18 , sejam elas com enfoque qualitativo 9,10 , quantitativo 6 ou quantiqualitativo 18 .…”
unclassified